2022
DOI: 10.1007/s44229-022-00004-z
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification of Potential Inhibitors of the SARS-CoV-2 Nucleocapsid Through Molecular Docking-Based Drug Repurposing

Abstract: SARS-CoV-2 is the virus responsible for the COVID-19 pandemic, and its effects on people worldwide continue to grow. Protein-targeted therapeutics are currently unavailable for this virus. As with other coronaviruses, the nucleocapsid (N) protein is the most conserved RNA-binding structural protein of SARS-CoV-2. The N protein is an appealing target because of its functional role in viral transcription and replication. Therefore, molecular docking method for structure-based drug design was used to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Porphyrin could spontaneously bind to the SARS-CoV-2 N-CTD (binding affinity energy of − 8.6 kcal/mol). The value is comparable to several COVID-19 antiviral candidates targeting the same viral protein, including silmitasertib (− 7.89 kcal/mol), fedratinib (− 8.2 kcal/mol), nintedanib (− 8.4 kcal/mol), dovitinib (− 8.6 kcal/mol), and rapamycin (− 8.9 kcal/ mol), even higher than TMCB (− 7.05 kcal/mol), lopinavir (− 6.58 kcal/mol), sapanisertib (− 6.14 kcal/mol), chloroquine (− 5.62 kcal/mol), Arbidol (− 5.32 kcal/ mol), oseltamivir (− 5.08 kcal/mol), ribavirin (− 4.86 kcal/ mol), favipiravir (− 4.44 kcal/mol), hydroxychloroquine (− 4.32 kcal/mol), and remdesivir (− 3.46 kcal/mol) [40][41][42]. Further, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porphyrin could spontaneously bind to the SARS-CoV-2 N-CTD (binding affinity energy of − 8.6 kcal/mol). The value is comparable to several COVID-19 antiviral candidates targeting the same viral protein, including silmitasertib (− 7.89 kcal/mol), fedratinib (− 8.2 kcal/mol), nintedanib (− 8.4 kcal/mol), dovitinib (− 8.6 kcal/mol), and rapamycin (− 8.9 kcal/ mol), even higher than TMCB (− 7.05 kcal/mol), lopinavir (− 6.58 kcal/mol), sapanisertib (− 6.14 kcal/mol), chloroquine (− 5.62 kcal/mol), Arbidol (− 5.32 kcal/ mol), oseltamivir (− 5.08 kcal/mol), ribavirin (− 4.86 kcal/ mol), favipiravir (− 4.44 kcal/mol), hydroxychloroquine (− 4.32 kcal/mol), and remdesivir (− 3.46 kcal/mol) [40][41][42]. Further, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al [53] demonstrated the ability to screen drugs inhibiting SARS-CoV-2 replication using pseudovirus, thus greatly reducing the risk of infection during experiments. For future works, we suggested the application of this coronaviral nucleocapsid-targeting DBSS approach to explore the antiviral activities of different types of bioactive compounds other than phytochemicals, such as microbial metabolites [54], and for drug repurposing endeavors [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…45 Since the beginning of the pandemic, some in silico studies have been conducted to identify potential SARS-CoV-2 nucleocapsid inhibitors using molecular docking-based drug repurposing. 46,47 At the same time, such research did not lead to the development of drugs of such a focus. One of the reasons for the failure of developing small-molecule therapeutics based on nucleocapsid proteins might be the lack of well-dened binding and catalytic sites.…”
Section: Nucleocapsid Protein (N Protein)mentioning
confidence: 99%